Three perspectives on parental support in youth soccer: Children, parents, and coaches - Lobinger, B.; Eckhardt, V. C.; Lautenbach, F. (International Journal of Sports Science & Coaching, 2021)
The aim of the research project was to gain an in-depth understanding of how children, coaches, and parents in youth soccer perceive parental support. In a preliminary study, a questionnaire was developed to assess satisfaction with parental support and sideline behavior in soccer. The multisection questionnaire was adapted to all three parties of interest—children, parents, and coaches—and administered to 260 parents, 196 coaches, and 111 male players aged 12-14 years across different clubs to identify factors influencing satisfaction with parental behavior across all three groups. Factor analysis led to a revised version of the questionnaire, emphasizing the importance of emotional support. The revised questionnaire was implemented in two consecutive field studies. Samples were drawn from an amateur youth soccer setting (Study 2, N = 316, players aged 8-13 years) and a professional youth academy (Study 3, N = 209, players aged 9-16 years). Overall, results indicate children and parents were highly satisfied with parental support and sideline behavior but coaches` satisfaction differed significantly. The discussion therefore includes all three perspectives and provides recommendations on how to improve the coach-parent relationship and professional engagement with parents.